I`ve seen this, so I`ve got this! Exploring the use of imagery and self-talk within action sports athletes - Young, P. R. (Journal of Human Performance in Extreme Environments, 2023)
The present study aimed to expand the current knowledge of psychological skills usage within athletes of action sports by exploring the use of imagery and self-talk within skateboarders and snowboarders. Skateboarders and snowboarders (N 5 74) completed the Athletic Coping Skills Inventory (ACSI-28; Smith et al., 1995), the Self-Talk Questionnaire (S-TQ) for sports (Zervas et al., 2007), and the Sport Imagery Questionnaire (SIQ; Hall et al., 1998). Results indicated that participants scored significantly higher than reported norms of traditional athletes (Smith et al., 1995) on the coping with adversity and goal-setting/mental preparation subscales of the ACSI-28, and to a similar degree to traditional athletes on the remaining subscales. However, participants scored significantly lower on the total score of the ACSI-28 than previously reported action sports athletes (Young & Knight, 2014). Participants scored significantly higher than reported norms of traditional athletes on the cognitive functional and motivational functional subscales of the S-TQ. On the SIQ, participants scored significantly lower than reported norms for traditional athletes (Hall et al., 2005) on the MG-M subscale, while scoring similarly to reported norms on the CG, CS, MS, and MG-A subscales. Results of the present study confirm that action sports athletes utilize psychological skills to a degree similar to that of traditional athletes, and that skateboarders and snowboarders specifically include the use of imagery and self-talk within their psychological skills arsenal.